Profil Resiliensi Remaja Putri di Panti Asuhan dilihat Pada Aspek Empathy, Emotion Regulation dan Self-Efficacy - Yenti Arsini; Nandang Rusmana; Nani Sugandhi (Kuras Institute, 2022)
This study aims to describe the resilience profile of adolescent girls at the Aisyah Muhammadiyah Orphanage, North Sumatera. In this study, we will discuss aspects of resiliensi in the daily lives of adolescents in orphanages which include the aspects of, a).Emotion, b).Impulse control, c).Optimistic. d).Causal analysis, d),Empathy, e).Self efficacy, f).Reaching out. There are 30 young womwn, 17 people at the junior high school level and 13 people at senior high school level. To obtain data in this study, interviews and guestionnaires related to aspects of resiliensi were carried out. From the results of the study, it was found that in general the resilience of adolescent girls was in the medium category as many as 28 peopel (93.3%), and the low category as many as 2 people (6.67%). From the results of this study, a guidance will be created for young women in orphanages in strengthening and growing strong resilience in facing various problems and challenges in the future.